Analisis Kepentingan Umum Dalam Asas Oportunitas Pada Sistem Peradilan Pidana - Iqbal, Muhammad; Ilham, Muhammad Azham (Program Studi Ilmu Hukum, Fakultas Hukum, Universitas Muslim Indonesia, 2022)
This research aims to examine and analyze the development and criteria of public interest in the principle of opportunity in the criminal justice system. The research uses normative legal methods by using statutory approaches, legal theories and opinions of legal experts with secondary, primary and tertiary legal materials. With this research the author obtains answers to the existing problems that the existence of the prosecutor as an institution that has the authority to set aside cases based on public interest to avoid abuse of authority and ensure legal certainty in order to apply the principle of opportunity based on public interest in the criminal justice system, the Attorney General sets aside in a letter of determination or provides a copy of the decision to set aside the case for the evidence concerned, that the case is set aside in accordance with the rules in the legislation After the revocation of Law No. 5 of 1961 replaced by Law No.5 of 1991 concerning the Attorney General of the Republic of Indonesia. 1991 concerning the Prosecutor's Office of the Republic of Indonesia, the setting aside of cases based on public interest in the principle of opportunity in the criminal justice system is still maintained in Article 32 letter c which clearly says: